2019
DOI: 10.1002/cam4.2443
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk association of CDKN1A and RET gene SNPs with medullary thyroid carcinoma: Results from the largest MTC cohort and meta‐analysis

Abstract: Background Medullary thyroid carcinoma (MTC) is a rare subtype of thyroid cancer. Other than gain‐of‐function RET mutations, no other genetic, lifestyle or environmental risk associations have been established for MTC. Several case‐control studies and meta‐analysis have examined the risk association of different SNPs with MTC in different populations but with contradictory or inconclusive results. Methods In a large cohort of 438 Indian MTC cases and 489 gender and ethnicity matched healthy controls from 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
0
13
1
Order By: Relevance
“…Since 12 patients with concomitant secondary variants R114H, T278N, and D489N presented with a relatively wide range of diagnostic ages, the clinical disease course remains uncertain and inconsistent. A cautious approach might be to remain aware of the possible concomitant presence of compound mutations when faced with an abnormal natural disease course or unusual clinical features; however, appropriate validation is needed to avoid misinterpretation and irreversible clinical consequences [ 25 , 29 , 30 , 37 , 38 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 12 patients with concomitant secondary variants R114H, T278N, and D489N presented with a relatively wide range of diagnostic ages, the clinical disease course remains uncertain and inconsistent. A cautious approach might be to remain aware of the possible concomitant presence of compound mutations when faced with an abnormal natural disease course or unusual clinical features; however, appropriate validation is needed to avoid misinterpretation and irreversible clinical consequences [ 25 , 29 , 30 , 37 , 38 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, however, were either mostly limited to RET SNP hotspots, reported controversial conclusions, or had not examined susceptibility [ 33 36 ]. These issues suggest the need for analysis of potential modifying factors, including the entire RET coding region, and an individualized strategy for clinical management of MEN2 should be considered [ 1 , 19 , 29 , 34 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abundant studies have yielded a robust evidence for a causal role of RET proto-oncogene mutation in the development of neoplastic CCH and the subsequent hereditary MTC [24][25][26]. Activating transcription factor 4 (ATF4) is shown to suppress MTC by targeting RET gene in vivo and in vitro [27].…”
Section: Discussionmentioning
confidence: 99%
“…Other pathogenic variants commonly observed in HTC lead to enhanced cell proliferation. These include pathogenic variants in the RAS family of oncogenes that are involved in controlling cell division, as well as mutations in the negative regulator of RAS pathway– NF1 (neurofibromatosis type 1) and CDKN1A (cyclin dependent kinase inhibitor 1A), which is involved in cell cycle regulation [ 32 , 35 , 36 , 37 ]. In addition, commonly mutated ATXN1 (antioxidant protein 1 homolog), involved in the regulation of the cell cycle and oxidative stress, may play a role in HTC oncogenesis [ 38 ].…”
Section: Genetic Alterations In Htcmentioning
confidence: 99%